Electronic Funds Transfer in the Bank Card Industry - Bruce E. Woodruff (Washington University Law Quarterly, 1977)
EFT is an excellent replacement for the check. Six billion dollars of float could be eliminated by creating a more efficient payment system. EFT is faster, more efficient, easier to use, and less susceptible to fraud and theft. In many areas of the country the check is useless to obtain cash. The law must now demonstrate that it is flexible enough to cope with electronic checks. If it does not allow banks to develop EFT systems, others, particularly retailers, will dominate the payments system by controlling EFT throughout the United States. In this Article, Bruce E. Woodruff discusses the application of the credit card (EFT) system to a bank debit card system with emphasis on the activities of Credit Systems, Inc. (CSI), a regional bank association. Its efforts at implementing a bank debit card EFT system were aborted because application of the relevant law is unsettled. It is unclear whether courts will interpret antitrust, banking, and commercial transaction (UCC) laws sufficiently liberally to accommodate new banking methods mandated by a national EFT system. The advantages to the public from such a system are tremendous, Woodruff claims, and urges courts to construe the laws as sufficiently flexible to encompass electronic checking. Cognizant that federal regulation would become increasingly important as EFT developed, Congress created a national commission in 1974 to devise a legislative program to control and encourage EFT development.
Keywords: Credit